La correcta valoración de la imputabilidad en trastornos de la personalidad dentro del sistema penal ecuatoriano mediante el estudio de casos - Andrade Miranda, Cinthya Melany (2023)
The present investigation has as a general objective to carry out a legal critical analysis on the assessment of imputability applied to those people with personality disorders, in the context of current legislation and the study of practical cases, for which it is analyzed through the doctrine, the theory, jurisprudence and academic referents the current state of the expertise and its assessment in relation to the disorders that a person may suffer and their imputability, considering that not proceeding appropriately can lead to a violation of the fundamental rights of the person investigated and the due process. The methodology applied in the present has a qualitative approach, the bibliographic descriptive type, with adherence to the inductive-deductive, analytical synthetic and exegetical methods, having as a technique the study of cases, for this they refer through the instrument of data sheets. cases, two forensic psychiatric appraisals and their report, from which the main indicators developed in the results are extracted and their discussion provide beginnings that lead to the conclusion that the psychiatric and psychological appraisals weigh when defining the state of conscience and will of the individual in the investigated infraction and thus determine if it is in effect attributable or not and its legal destination, it is these indicators that define the participation and circunstances of the infraction and thus with a correct assessment it will be before the guardianship and guarantee of rights and a reasoned and proportional decision.